Proyecto de mejoramiento de la gestión de talento humano enfocado a los subsistemas de reclutamiento, selección e inducción, del área administrativa del Hospital 'Padre Carollo un Canto a la Vida - Castillo Calderón, Daysi Alexandra (2015)
This project contains a procedures manual, which is designed as a practical guide to the Human Resources Department of the Tierra Nueva Foundation, Hospital Padre Carollo " Un canto a la Vida ", when required subsystems Organizational Development: recruitment, selection and induction; Simultaneously, a manual functions needed to from the Human Resource Management states, restructuring systems, organization, procedures and methods. This proposal has been developed keeping the routing of the strategic plan of the institution, which, attached to providing a good quality service and warmth to the most vulnerable sectors, required to achieve this objective, have a department of Resources human well-structured, seeing reflected in the efficiency and effectiveness of employees and especially in meeting the goals.